Multiple plasmon-induced transparencies in coupled-resonator systems - Chen, Jianjun; Chen Wang; Zhang, Ru; Xiao, Jinghua (Optics Letters, 2012)
Multiple plasmon-induced transparencies are numerically predicted in an ultracompact plasmonic structure, comprising series of stub resonators side-coupled with a metal-isolator-metal waveguide. Because of the phase-coupled effect, electromagnetically induced transparency (EIT)-like spectral response occurs between two adjacent stub resonators with detuned resonant wavelengths. In this approach, multiple EIT-like spectral responses, with bandwidths of the order of several nanometers, are obtained in the plasmonic structure with a small footprint of about 0.6 mu m(2). An analytic model and the relative phase analysis based on the scattering matrix theory are used to explain this phenomenon. (C) 2012 Optical Society of America